Cs ION EXCHANGE CAPACITY OF ZEOLITE BAYAH, LAMPUNG, AND TASIKMALAYA - Noviarty Noviarty; Dian Anggraini; Arif Nugroho (Jurnal Zeolit Indonesia, 2009)
Cs ions exchange process has been conducted on natural zeolite (from Bayah, Lampung, and Tasikmalaya) which was activated with ammonium chloride. NH4-zeolite which was formed, is used to exchanger or absorber material of Cs ions. The duration of ions exchange process was optimized by varying the stirring time of 1 hours, 2 hours, 3 hours, 4 hours, 5 hours, and 24 hours. In all three zeolite types was obtained the optimization process time are the contact time of 1 hours. Cation exchange capacity (CEC) of natural zeolite was determined by standard methods. Attempts to obtain a monocation zeolite as a NH4-zeolite effectively acquired about 88% which used as a exchanger or absorber Cs ions. The effectiveness of Cs ions Cation exchange capacity with the ammonium was determined by batch-exchange for 1 hour. The calculation result o effectiveness CEC-Cs are 1.4269 Meq/gram ± 0.0397, RSD: 2.79% for Bayah zeolite, 1.4476 Meq/gram ± 0.0103, RSD: 0.71% for Lampung zeolite, 1.4044 Meq/gram ± 0.0050, RSD: 0.36% for Tasikmalaya zeolite. Stability of Cs-zeolte bond against heat treatment was tested at temperature of 25°, 300°, 600 °, 900°, and 1200 °C. The result showed that the relea se of Cs-ions is not significant from zeolite structure. The heating below 900°C, the release of Cs-ions jus t occurs on the surface (it was not change the initial of zeolite structure), whereas above that temperature was occurs the changed of zeolite structure, although there was not visible the release of Cs-ions on leaching process at the water. The conclusion is all three types of natural zeolite was potentially to be used as Cs-ions isolate which is especially useful to absorbing Cs-radioactive isotope as a result from fission of nuclear fuel element.